Disruptive Innovation in Muslim Fashion: The Rise of White Label Business Models in Expanding Market Access - Ibnu Asikin, Ridwan (Jurnal Inovasi Ekonomi, 2025)
Disruptive innovation has become an inevitable force shaping modern industries, including the Muslim fashion sector. This study examines the challenges and opportunities arising from the adoption of white label business models in Muslim fashion. The white label concept enables entrepreneurs to establish their own brands without engaging directly in production processes, as manufacturers provide designs, materials, and product development. This model enhances efficiency, reduces operational costs, and lowers entry barriers for new market participants. However, the rapid growth of digital technology and e-commerce also intensifies competition, accelerates changing consumer preferences, and challenges businesses to maintain customer loyalty. At the same time, disruptive innovation creates significant opportunities, such as broader market access, product diversification, and strategic collaborations through digital platforms. From a sharia economic perspective, this model aligns with permissible trade practices, provided it adheres to ethical principles and avoids elements such as fraud and injustice. This study concludes that the white label business model offers a flexible and scalable strategy for entrepreneurs to respond to disruption in the Muslim fashion industry. Success in this sector depends on the ability to balance efficiency in production with strong branding, innovation, and customer engagement in an increasingly competitive digital marketplace.